The relationship between responsive caregiving and child outcomes: evidence from direct observations of mother-child dyads in Pakistan - Elissa Scherer; Ashley Hagaman; Esther Chung; Atif Rahman; Karen O'Donnell; Joanna Maselko (BMC, 2019)
Abstract Background Responsive caregiving, or interactions in which caregivers give appropriate responses to a child's signals, is linked to improved psychosocial, cognitive and physical outcomes in children. However, much remains unknown about how responsive caregiving affects child development across cultural and socioeconomic contexts. The purpose of this study is to examine predictors of maternal responsive caregiving and investigate how these interactions are associated with children's development. Methods Data for the current analyses came from a longitudinal study designed to follow mothers from the third trimester through the first three years of the child's life. To assess responsive caregiving, the Observation of Mother-Child Interaction (OMCI) measure was used to examine maternal and child behaviors during a 5-min picture book activity at 24 months. Outcomes included child height-for-age z-score and child socioemotional development, using the Ages and Stages Questionnaire-Socioemotional (ASQ-SE) in which lower scores demonstrated better development. Using mean comparisons, the effects of baseline sociodemographic factors and maternal depression on responsive caregiving were tested. Analyses utilized hierarchical linear regressions to examine cross-sectional associations between responsive caregiving and child development outcomes at 24 months. Additional analyses controlled for the Home Observation for Measurement of the Environment (HOME), a common measure in low-income contexts of caregiving, to assess whether OMCI was uniquely predictive of child outcomes. Results Higher maternal education attainment, lower number of children, greater socioeconomic assets, and lack of maternal depression were associated with higher levels of observed responsive caregiving behaviors. Higher total OMCI scores were associated with positive child socioemotional outcomes in adjusted models (β: -0.84, 95% CI [− 1.40, − 0.29]). The finding was statistically significant, even after controlling for HOME score (β: -0.83, 95% CI [− 1.38, − 0.27]). There was no association between OMCI scores and child linear growth. Conclusions Responsive caregiving is linked to positive child socioemotional development in rural Pakistan. Our findings suggest that incorporating responsive caregiving into child health interventions in LMIC may have valuable impacts on child socioemotional development. The OMCI may be useful in identifying important pathways for change to responsive caregiving behaviors and may be of service for future interventions that optimize child development through responsive caregiving. Trial registration NCT02111915 (09/18/2015); NCT02658994 (01/22/2016). Trials were prospectively registered.